2020
DOI: 10.3390/su12062425
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Land Use and Topographic Position on Soil Organic Carbon and Total Nitrogen Stocks in Different Agro-Ecosystems of the Upper Blue Nile Basin

Abstract: Soil organic carbon (SOC) and total nitrogen (TN) are key ecological indicators of soil quality in a given landscape. Their status, especially in drought-prone landscapes, is associated mainly with the land-use type and topographic position. This study aimed to clarify the effect of land use and topographic position on SOC and TN stocks to further clarify the ecological processes occurring in the landscape. To analyze the status of SOC and TN, we collected 352 composite soil samples from three depths in the up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 70 publications
5
34
0
Order By: Relevance
“…In the examination by Fang et al [64], SOC in forest land increased with altitude and levels were significantly different at 0-200 and 400-800 m in the 10-30 cm soil layer. Similar results were obtained by Abebe et al [65], where SOC stock in bushland was the highest (166.22 Mg ha −1 ) in the upper position.…”
Section: Effect Of Topographic Position and Soil Depth On Soc Contentsupporting
confidence: 90%
See 1 more Smart Citation
“…In the examination by Fang et al [64], SOC in forest land increased with altitude and levels were significantly different at 0-200 and 400-800 m in the 10-30 cm soil layer. Similar results were obtained by Abebe et al [65], where SOC stock in bushland was the highest (166.22 Mg ha −1 ) in the upper position.…”
Section: Effect Of Topographic Position and Soil Depth On Soc Contentsupporting
confidence: 90%
“…In contrast, numerous studies have confirmed carbon leaching through erosion related to topography [65][66][67][68]. With increasing slope, infiltration decreases because the increasing slope area and the velocity of the water flow lead to increasing runoff.…”
Section: Effect Of Topographic Position and Soil Depth On Soc Contentmentioning
confidence: 99%
“…Compared to the use of DEM in the above-mentioned studies, the effects of the terrain features on the spatial patterns of grassland soil respiration were scarcely studied. Cultivated areas, grazed or restored grassland vegetation types with different aspects and slope positions have mostly been analysed for soil organic carbon, total nitrogen or other nutrient distribution/accumulation/erosion as well as patterns of above and belowground biomass [36][37][38][39][40] . These studies provided evidence for the effects of these terrain features on the differences in the spatial patterns of the soil nutrients or plant biomass, both influencing R s spatio-temporally.…”
mentioning
confidence: 99%
“…Empirically, this is true that SOC stocks generally increase as the mean annual temperature decreases (Stockmann et al, 2013). It has also been shown that less soil disturbance, greater vegetation cover, and organic input from grazing animals would improve the SOC in the highland areas (Abebe et al, 2020). The ndings show the need for climate-smart land management practices that contribute to soil organic carbon stock and at the same time reducing its emission from croplands and grasslands of the study area.…”
Section: Resultsmentioning
confidence: 67%
“…The show that soil carbon sequestration in croplands is small, which is also true in this study. Particularly in the highland areas, the SOC content in cropland was signi cantly increased from the upper to lower topographic positions (Abebe et al, 2020). This is because the upper lands are often exposed to soil erosion, serving as a source of runoff and sediment for the lower positions .…”
Section: Resultsmentioning
confidence: 99%